Psoriasiform Digital Bowen’s Disease: A Diagnostic Challenge and Short-Term Response to Liquid Nitrogen Cryotherapy - Putu Resika Melarosa; Ketut Kwartantaya Winaya; Lettisia Amanda Ruslan; Made Sri Adnyasitarini; Putu Ayu Paramitha Saraswaty (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Bowen’s disease (BD), or squamous cell carcinoma in situ, classically presents as a slowly enlarging erythematous plaque on sun-exposed skin. However, digital Bowen’s disease represents a distinct and rare clinical subset that frequently poses a significant diagnostic dilemma. Due to its unique anatomical location and morphological variability, digital BD often masquerades as benign inflammatory dermatoses, particularly psoriasis or chronic eczema, leading to dangerous therapeutic delays. Case presentation: We report the case of a 46-year-old male presenting with a solitary, rough, erythematous plaque on the dorsal aspect of the left index finger that had persisted for one year. The lesion was initially misdiagnosed and treated as an inflammatory condition without success. Detailed dermoscopic evaluation revealed a specific "psoriasiform" vascular pattern characterized by clustered glomerular vessels and surface scaling, raising suspicion for malignancy. Histopathological analysis confirmed the diagnosis of Bowen’s disease, demonstrating full-thickness epidermal atypia with psoriasiform hyperplasia. Notably, the presence of histological koilocytic atypia suggested a potential synergistic etiology involving Human Papillomavirus (HPV) infection alongside chronic ultraviolet exposure. The patient was treated with a tissue-sparing protocol of liquid nitrogen cryotherapy to preserve digital function. Conclusion: Complete clinical resolution of the lesion was observed at the three-week follow-up interval, resulting in a hypopigmented macule with full preservation of joint mobility. This case highlights the critical necessity of distinguishing "psoriasiform" malignancies from true inflammatory diseases through the recognition of specific vascular arrangements in dermoscopy. Furthermore, it suggests that cryotherapy is a pragmatic, function-sparing alternative to surgical excision for digital malignancies, provided that rigorous long-term surveillance is maintained to monitor for recurrence.